Peran Guru PAI dalam Mencegah Radikalisme di SMK Nurul Huda Desa Gingging, Kecamatan Bluto, Kabupaten Sumenep - Zeinul Ubbadi; Ashari Ashari (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
His research uses a type of field research (field study) using a qualitative approach. PAI teachers at Nurul Huda Vocational School play an important role in preventing radicalism. He designed a radicalism prevention program in three parts, namely Prevention, Supervision and Development. Not all activities he plans can be implemented well. However, in general the activities carried out by PAI Vocational School Teacher Nurul Huda are sufficient to describe himself as a teacher, guide, trainer and educator. 6 activities lead to confinement as a Teacher, 3 activities direct to confinement as a Guide, 5 activities direct to confinement as a Trainer, and 3 activities direct to confinement as an Educator. Second, there are obstacles in implementing the radicalism prevention program designed and implemented by PAI teachers at Nurul Huda Vocational School. These include the minimal ability of students to write scientific papers, the lack of audio-visual facilities, no funds allocated by schools for radicalism prevention programs, minimal internal motivation within students, and the internet which allows students to be exposed to radicalism at any time.